1995
DOI: 10.2307/3236393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, light and gibberellic acid on the germination of seeds of 43 species native to Western Australia

Abstract: Abstract. Species native to the southwest of Western Australia, representing a range of plant families, life‐history strategies, fire‐response syndromes, seed‐store types and seed weights, were tested for viability using tetrazolium chloride and for germination under combinations of constant temperatures of 15 °C or 23 °C, constantly dark or 12 h diurnal whitelight conditions, and with, or without, addition of gibberellic acid (GA3, 50 mg/l). Species previously known to require a heat‐shock treatment to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 31 publications
9
121
1
1
Order By: Relevance
“…This fact suggests that pine adaptation to perturbations must be sustained not in dormancy characteristics or structural properties that prevent immediate germination of seeds as is usual in Mediterranean plants [7,8,24,56], but in other adaptive responses.…”
Section: Resultsmentioning
confidence: 99%
“…This fact suggests that pine adaptation to perturbations must be sustained not in dormancy characteristics or structural properties that prevent immediate germination of seeds as is usual in Mediterranean plants [7,8,24,56], but in other adaptive responses.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds of species having a requirement for temperature fluctuation are much more likely to have dormancy enforced on them than seeds of species without such a requirement, in view of the relatively small amplitude of diurnal fluctuations of soil temperature that occurs beneath an established sward (Thompson et al 1977). Bell et al (1995) suggested that the ability to detect light is a mechanism that allows seed to discern between the buried and the unburied state. As significant quantities of light rarely penetrate greater than 5 mm of soil surface (Tester and Morris 1987), L. chinensis seeds that experience light condition and germinate would probably be on the soil surface in natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, mechanisms that minimize the risk will be under strong selection pressure (Meyer et al 1997), with natural selection favouring seed germination patterns that increase the probability of successful seedling establishment. For example, although temperature is not considered to be a limiting factor for recruitment in Mediterranean-type ecosystems (Lloret et al 2004), germination generally coincides with early winter when temperatures are low (typically 10-15°C; Bell 1999) and rainfall is reliable (Mott 1972;Bellairs & Bell 1990;Bell & Bellairs 1992;Bell et al 1995). This maximizes the period of root development prior to summer drought, thereby increasing seedling survival (Bell 1999).…”
Section: Introductionmentioning
confidence: 99%